Literatur review: Analisis perbandingan literasi sejarah di Australia dengan Indonesia - Nafi'ah, Ulfatun; Purwanta, Hieronymus (Universitas Negeri Malang, 2024)
Abstract This article aims to compare historical literacy in Australia with Indonesia. The purpose of writing the article is to understand the similarities and differences in historical literacy in Australia and Indonesia. This study uses a literature review method on Scopus journal. Articles published between 2010-2024. The results were 36 documents about historical literacy in Australia and 13 journal articles about historical literacy in Indonesia. A total of 20 articles were analyzed in more depth because they were appropriate to the topic. The result is that historical literacy in Indonesia is still low, both at secondary and tertiary levels. The goals of historical literacy in Australia and Indonesia have similarities, namely increasing students' historical awareness of the concept of critical historical thinking. The use of digital media is important to improve historical literacy, in Indonesia using various digital media such as the web, historical YouTube, films, e-modules, and multimedia. In Australia, movies and e-books are used. For learning methods in Australia, the PAPA model, and receptive and productive models are applied. In Indonesia, increasing historical literacy uses the